Pendidikan Kesehatan Pada Remaja Sadar Gizi Untuk Pencegahan Kekurangan Energi Kronik Dalam Menurunkan Angka Kematian Ibu - Riski, Merisa; S, Susilawati; Ariyani, Yulinda (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Lack of maternal knowledge about Chronic Energy Deficiency is one of the indirect causes of maternal and infant mortality. The purpose of this activity is to provide Nutrition Awareness Education for Teenagers to Prevent Chronic Energy Deficiency (KEK). The method of implementing this Community Service Program is community education in the form of health counseling, evaluated by pre-test and post-test. The method of implementing the service is to provide nutrition awareness education for teenagers by means of discussions using ebooklet media about balanced nutrition and KEK. The number of participants who attended was 50 people, 2 students, and 5 midwives. The activity started from the planning, implementation, evaluation, to the preparation of the report. The results of the activity showed a change in knowledge with an average pre-test of 90% of participants' knowledge being in the poor category and the post-test results of 90% being in the good category. In the skill aspect, all participants who attended (100%) were able to Know nutritional awareness for the prevention of KEK. Conclusion. Educational activities about nutritional awareness for the prevention of KEK can be an effort to increase knowledge and promote nutritional health in the prevention and control of KEK. It is hoped that this activity can become a health promotion strategy in the prevention and control of KEK.